Constitutional status of the Russian State Council in the mirror of actual constitutional reforms - O. A. Kozhevnikov; A. V. Bezrukov; A. N. Meshcheryakov (Правоприменение, 2021)
The subject of research is social relations concerning the constitutional transformation of the State Council of the Russian Federation into the format of a constitutional state body, it’s tasks and functions in the unified system of public power. The aim of the research is to confirm or disprove hypothesis that the Russian State Council is a constitutional state body that ensures the coordinated functioning and interaction of authorities in the unified system of public power.The methodological basis of the research includes historical, comparative legal, formal legal methods, legal modeling and forecasting. The research is based on existing and historical legal acts, materials of judicial practice, as well as on the works of leading national lawyers.The main results, scope of application. The authors substantiate concept of the constitutional status of the Russian State Council as a completely new constitutional state body, formed on the basis of modern national principles of state building, taking into account the existing constitutional practice. Main task of the State Council is exercising the constitutional powers of the Russian President to ensure the coordinated functioning and interaction of public authorities, the definition of the main directions of national and foreign policy of the state. The article provides a critical analysis of the goals, tasks, functions of the Russian State Council, the decisions it makes, as a result of which a number of conflicts in the regulation of its constitutional-legal status are revealed. Some proposals to improve legislation and law enforcement practice aimed at solving of the discovered contradictions are made. Current constitutional of the State Council is a result of the constitutional amendments of 2020 in the Russian Constitution and innovations in the Federal Law on the State Council of the Russian Federation. The authors substantiate the idea that the consolidation of a new constitutional position of the State Council can be considered as a process of forming a completely new state body, designed to ensure the coordinated functioning and interaction of bodies included in the unified public system. A comparative legal analysis of the constitutional legislation on State Councils in foreign countries showed that despite the same name the status and functions of these state institutions differ greatly in different countries, therefore any comparative study of them will be unreliable.Conclusions. The Russian State Council has competence, functions of a state power character, take decisions signed by the President of the Russian Federation and therefore have a generally binding character. So it has the characteristics of a public authority. The Russian State Council is a new constitutional and legal structure - a constitutional state body created in order to implement the constitutional powers of the Russian President to ensure the coordinated functioning and interaction of other bodies (that are part of the unified system of public authority) and to determine the main directions of domestic and foreign policy of the state.